Roofless Space: Indigenous Engagement in The Semarang Colonial Exhibition, 1914 - Afrida Hadmah; Nanda Julian Utama (Criksetra: Jurnal Pendidikan Sejarah, 2025)
The presence of international exhibitions in the colonies was often organized by countries in Europe in the late 19th and early 20th centuries. Semarang, in particular, once hosted the Colonial Exhibition, conceptualized in a modern way to introduce elements of modernity to the colonies. This research aims to examine the extent of indigenous participation in the colonial exhibition held in Semarang in 1914. The temporal scope is set in 1914 because that year became the time of the implementation of the Colonial Exhibition, which had previously been delayed several times. Using historical research methods in the form of heuristics by collecting primary and secondary sources. Primary sources used include Gedenkboek van de Koloniale Tentoonstelling Semarang, August 20 - November 22, 1914 and Officieele Catalogus Koloniale Tentoonstelling Semarang 1914. Followed by verification, interpretation, and historiography. The findings show that the organization of the Semarang Colonial Exhibition also involved all layers, from the top to the bottom. In fact, a special room was designed to attract indigenous visitors and set with a cheaper ticket price than other visitors. However, this did not result in an increase in indigenous visitors, and in fact was far from what was expected. Moreover, the organization of the Colonial Exhibition in Semarang contributed to the development of Semarang's southern district.